2018
DOI: 10.1055/s-0044-101546
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Threshold Power in Cyclists: Validity of the Concept and Physiological Responses

Abstract: Functional threshold power is defined as the highest power output a cyclist can maintain in a quasi-steady state for approximately 60 min (FTP). In order to improve practicality for regular evaluations, FTP could theoretically be determined as 95% of the mean power output in a 20-min time trial (FTP). This study tested this assumption and the validity of FTP and FTP against the individual anaerobic threshold (IAT). Twenty-three trained male cyclists performed an incremental test to exhaustion, 20- and 60-min t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 26 publications
3
62
1
Order By: Relevance
“…Thus, caution is warranted when comparing POs at MLSS and CP in relation to that derived from FTP testing. Given the great variability in measures of FTP compared to other markers of critical intensity, caution should be exerted before using FTP95% as one size fits all approach to predicting critical intensities of exercise 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, caution is warranted when comparing POs at MLSS and CP in relation to that derived from FTP testing. Given the great variability in measures of FTP compared to other markers of critical intensity, caution should be exerted before using FTP95% as one size fits all approach to predicting critical intensities of exercise 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This is pertinent as many regard MLSS to be the criterion measure for tolerable exercise 2 . Furthermore, although cross-sectional comparisons between FTP95% and other markers of performance have been made [5][6][7]9 , no study has evaluated the ability or sensitivity of the FTP95% test to track changes in fitness level on a longitudinal basis.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the key metric in a series of calculations of training load and exercise intensity (i.e., training stress score [TSS], intensity factor [IF]) [6]. Moreover, FTP is used as an indirect and practical estimate of the anaerobic threshold (AnT) and maximal lactate steady state (MLSS) [7][8][9]. Due to the long test duration (i.e., 60 min), it was suggested that the FTP might be determined as 95 % of the mean PO in a 20-min TT (FTP 20 ) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The first step is the specific 45-min warm-up, which includes a maximum effort 5-min TT [6]. To the best of our knowledge, Borszcz et al [7,8] and Valenzuela et al [10] are the only studies that have used the warm-up recommended by the authors [6]. Others have not used this section of the protocol [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation